Media DW Learn German terhadap Kemampuan Menyimak Bahasa Jerman - Tandriani, Megri; Rijal, Syamsu; Anwar, Muhammad (Academic : Journal of Social and Educational Studies, 2024)
Abstract. The purpose of this study was to determine the effectiveness of DW Learn German media on student's German listening skills. The subjects in this study were students of class XI SMAN 9 Makassar which amounted to 25 students. This research uses experimental research method with the research design used is pre-experiment one group pre-test-posttest. The test questions are in the form of multiple choice with the number of questions for each test is 10 questions. Data were analyzed using the N-Gain test. From the data analysis, the average pre-test result was 34 and the average post-test result was 76.80. The acquisition of the N-Gain value from each student, there were 9 students (36%) in the high N-Gain category, in the medium N-Gain category there were 15 students (60%) and in the low N-Gain category there were 1 student (4%). The percentage result of N-Gain effectiveness from 25 students is 64.84%. This shows that the use of DW Learn German media is quite effective in improving student listening skills.Keywords: Effectiveness, DW Learn German, Media, Listening Skills